Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The benefits of a nurse plant, shade cloth, and nurse rock on Carnegiea gigantea (saguaro) growth and survival shift along a stress gradient - Helen I. Rowe; Mary Fastiggi; Debbie Langenfeld; Scott Milne; John Parente; Giavanna Raboin; Nikhil Sethi; Madelaine Stockman; Melanie Tluczek (Journal of Arid Environments, 2026)

Different responses of Pinus sylvestris L. and Larix decidua Mill. to forest fire in Central England (UK) - Francesco Niccoli; Luigi Marfella; Jerzy P. Kabala; Jon Rowe; Rossana Marzaioli; Flora A. Rutigliano; Helen C. Glanville; Giovanna Battipaglia (Agricultural and Forest Meteorology, 2025)

Accounting for the uncertainty in nitrogen deposition estimates in support of policy - Huw Woodward; Elizabeth Ramos Fonseca; Tim Oxley; Ed C. Rowe; Massimo Vieno; Eiko Nemitz; Helen ApSimon (Environmental Research, 2025)

Mid-term (5 years) impacts of wildfire on soil chemical and biological properties in a UK peatland - Luigi Marfella; Mark A. Ashby; Georgia Hennessy; Jon Rowe; Rossana Marzaioli; Flora A. Rutigliano; Helen C. Glanville (Applied Soil Ecology, 2025)

Sustainability of bioenergy – Mapping the risks & benefits to inform future bioenergy systems - Andrew James Welfle; Alberto Almena; Muhammad Naveed Arshad; Scott William Banks; Isabela Butnar; Katie Jane Chong; SamuelJ.G. Cooper; Helen Daly; Samira Garcia Freites; Fatih Güleç; Christopher Hardacre; Robert Holland; et al. (Biomass and Bioenergy, 2023)

Comparing common Buffelgrass (Pennisetum ciliare) removal techniques: cost efficacy and response of native plant community - Helen I. Rowe; Tiffany A. Sprague; Mary Fastiggi; Paul Staker (Biological Invasions, 2023)

Industrial ecology for the oceans - Ian Vázquez‐Rowe; Robert Parker; Helen Hamilton; Huan Liu (Journal of Industrial Ecology, 2022)

Comparing common fountain grass removal techniques: cost efficacy and response of native plant community - Helen I. Rowe; Tiffany A. Sprague; Paul Staker (Biological Invasions, 2022)
Fountain grass ( Pennisetum setaceum ) is a globally pervasive invasive species and a prime example of an escaped horticultural ornamental. In areas where it is not naturally found, it displaces native plant communities and disrupts ecological systems and processes. Cost-effective removal efforts that protect the native plant community are needed for its control. We conducted an experiment from March 2018 to March 2021 in 5 m × 5 m plots to test the efficacy and record costs for common removal techniques (cut and herbicide, herbicide one or two times per year, manual removal) in the Sonoran Desert, Arizona, United States. Each treatment took 2.5 years to achieve control in the plots, and treatments did not negatively affect the native plant community. The response of native plants was mediated by year, such that native cover in treatment plots recovered to similar levels as uninvaded control plots with sufficient rainfall. Plots that received the manual removal treatment had almost five more native plant species than the invaded control treatment (22.7 ± 1.63 compared to 18.1 ± 1.61). Herbicide applied in spring and fall increased efficacy of removals in the first year but was not significantly different from the other treatments averaged over year. Herbicide once per year was most cost effective across different sized areas. Manual removal was also cost effective in small areas (

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Toward an understanding of broad-scale patterns of the habitat suitability of fountain grass (Cenchrus setaceus (Forssk.) Morrone, Poaceae) - Fábio Albuquerque; Miguel Á. Macías-Rodríguez; Alberto Búrquez; Helen Rowe (Plant Ecology, 2020)

Integrating legacy soil phosphorus into sustainable nutrient management strategies for future food, bioenergy and water security - Helen Rowe; Paul J. A. Withers; Peter Baas; Neng Iong Chan; Donnacha Doody; Jeff Holiman; Brent Jacobs; Haigang Li; Graham K. MacDonald; Richard McDowell; Andrew N. Sharpley; Jianbo Shen; et al. (Nutrient Cycling in Agroecosystems, 2016)

Female choice and the relatedness of mates in the guppy (Poecilia reticulata) - Trevor E. Pitcher; F. Helen Rodd; Locke Rowe (Genetica, 2008)